The Otago Exercise Training Program For Patients With Moderate Fall Risk Problems : A Case Report - Mambangsari, Citra; Basiroh, Siti; Haroen, Hartiah (Universitas Muhammadiyah Surakarta, 2024)
The elderly are a vulnerable group because they have experienced various setbacks. Degenerative disorders are physiological processes that occur in the elderly, one that often occurs is a decrease in the function of the musculoskeletal system such as complaints of joint pain, decreased muscle strength, and decreased balance which can cause the risk of falling. The management that can be done to prevent falls while minimizing side effects is by using non-pharmacological therapies, one of which is by doing the Otago Exercise. The purpose of this case study is to explain how the effect of Otago Exercise is to prevent the risk of falling in the elderly. The writing method used in this study is to use a case study conducted on the elderly Mrs. S. The results of nursing care after carrying out the Otago Exercise Program showed an increase in the risk of falling in the elderly from 32 to 39. This Otago Exercise has been proven to be effective and can be done to prevent the risk of falling in the. The elderly can implement the Otago Exercise Program on an ongoing basis accompanied by officers at the orphanage to prevent falls and maintain a balance so that joint function and posture remain good.